A study on third-party logistics in India. (1st January 2013) - Rajesh, R.; Pugazhendhi, S.; Ganesh, K.
The outsourcing is becoming increasingly popular because of openness, globalisation and high efficiency. Among the various functions in organisation, the change in trade mode via outsourcing is predominantly potential in the logistics function than the other activities. The concept of third-party logistics (3PL) service provider refers to the external organisation to perform the logistics functions that have customarily been performed within an organisation. This research work focuses on carrying out a comprehensive study on 3PL practices in India, the opportunities and threats for 3PL business in India through a questionnaire-based survey, and on performing analysis with the purpose of gaining more insight into these aspects.